The grand seduction [videorecording (DVD)] - Gleeson, Brendan; Pinsent, Gordon; Balaban, Liane, 1980-; Kitsch, Taylor, 1981- (Entertainment One, 2014)
A small fishing village must procure a local doctor to secure a lucrative business contract. When unlikely candidate and big city doctor Paul Lewis lands in their lap for a trial residence, the townsfolk rally together to charm him into staying. As the doctor's time in the village winds to a close, acting mayor Murray French has no choice but to pull out all the stops and begin The Grand Seduction.